CHARACTERISTICS OF OTHER ANXIETY DISORDERS IN INPATIENTS WITH ACUTE CORONARY SYNDROME AT THE NATIONAL HEART INSTITUTE, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of other anxiety disorders (F41) in inpatients with acute coronary syndrome at the National Heart Institute, Bach Mai Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 206 patients with acute coronary syndrome diagnosed according to the ICD-10 criteria.Results: The research results showed that 29.6% of patients with acute coronary syndrome had other anxiety disorders (F41). Within this group, generalized anxiety disorder accounted for the highest proportion (41%), followed by other mixed anxiety disorders (26.2%). Autonomic arousal symptoms constituted the highest proportion among the symptom clusters of other anxiety disorders (88.9%).Conclusion: Other anxiety disorders (F41) are prevalent among patients with acute coronary syndrome. Among these, generalized anxiety disorder is the most common subtype. Early detection and accurate diagnosis play a crucial role in improving the quality of life and reducing the burden of care.
Keywords: Acute coronary syndrome, other anxiety disorders, F41, generalized anxiety disorder.